Islamic ethics of creativity and innovation in biomedical sciences - Malik, Mohammad Manzoor (2014)
Creativity and innovation is very part of human nature (fitrah) which makes human beings different from and special among other beings. Islam gives very high importance to health as evidenced in the Quran and the Sunnah, and Muslim civilization that flourished in Bagdad and Spain made original contributions to medicine including diagnosis, pharmacology, and medical technology. Muslim civilization is different from all world civilizations because it developed only what was beneficial and harmless, that is why there is no such record that may show any significant contribution of Muslims to inventing and discovering poisons and destructive weaponry. Muslims were led by Islamic ethical spirit in pursuing and creating knowledge generally. Whereas, the contemporary developments in biomedical sciences have been flourishing in the circles where science is understood to be ethics-free, neutral, and value-free. This approach has given birth to many new biomedical issues such as cosmetic surgery, in vitro fertilization, artificial insemination, sterilization, human cloning,sex reassignment surgery, gene mutation, neural coding, recombinant DNA technology, gene doping, human genetic engineering, and human experimentation in medical research. Some of these issues may be beneficial if guarded by appropriate ethics, yet some of these issues create space to question their very creation. After discussing the ethical repercussions of these issues, a general ethical framework is formulated on Islamic guidelines for creativity and innovation in biomedical sciences.